Effect of Tongxinluo on Podocyte Apoptosis via Inhibition of Oxidative Stress and P38 Pathway in Diabetic Rats. (8th September 2016) - Cui, Fangqiang; Gao, Yanbin; Zhao, Wenjing; Zou, Dawei; Zhu, Zhiyao; Wu, Xiaoming; Tian, Nianxiu; Wang, Xiaolei; Liu, Jing; Tong, Yu
Abstract : Diabetic nephropathy (DN) has been the leading cause of end-stage renal disease (ESRD). Podocyte apoptosis is a main mechanism of progression of DN. It has been demonstrated that activated P38 and caspase-3 induced by oxidative stress mainly account for increased podocyte apoptosis and proteinuria in DN. Meanwhile, Tongxinluo (TXL) can ameliorate renal structure disruption and dysfunction in DN patients in our clinical practice. However, the effect of TXL on podocyte apoptosis and P38 pathway remains unclear. To explore the effect of TXL on podocyte apoptosis and its molecular mechanism in DN, our in vivo and in vitro studies were performed. TXL attenuated oxidative stress in podocyte in DN in our in vivo and in vitro studies. Moreover, TXL inhibited the activation of P38 and caspase-3. Bcl-2 and Bax expression was partially restored by TXL treatment in our in vivo and in vitro studies. More importantly, TXL decreased podocyte apoptosis in diabetic rats and high glucose cultured podocyte. In conclusion, TXL protects podocyte from apoptosis in DN, partially through its antioxidant effect and inhibiting of the activation of P38 and caspase-3.